Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan dan Inflasi terhadap Profitabilitas pada Perusahaan Farmasi dan Kesehatan Terdaftar di BEI Periode 2019-2023 - Karina Wahyu; Sri Wahyuning (LPPM Universitas Sains dan Teknologi Komputer, 2026)
This study analyzes the effect of firm size, sales growth, and inflation on profitability as proxied by Return on Assets (ROA) in pharmaceutical and healthcare sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs a quantitative approach with descriptive and causal designs. The sample was determined using a purposive sampling technique based on predefined criteria, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that firm size has a negative and significant effect on ROA, sales growth has a positive but not significant effect on ROA, and inflation has a negative and significant effect on ROA. Simultaneously, the three independent variables have a significant effect on ROA. The Adjusted R Square value of 0.912 indicates that 91.2% of the variation in ROA can be explained by the model, while the remaining 8.8% is influenced by other variables outside the study. These findings confirm that profitability is affected by a combination of internal and external factors; therefore, improvements in operational efficiency and adaptive strategies to economic conditions are required to maintain financial performance stability.